Multiple esophageal hematomas with oozing observed and successfully treated after transcatheter mitral valve edge‐to‐edge repair procedure. Issue 1 (24th November 2021) - Shirai, Yasuyuki; Kinoshita, Yoshihiro; Koumoto, Tatsuya; Kawano, Michitaka; Ogoshi, Ayako; Harada, Katsunori; Isotani, Akihiro; Shirai, Shinichi; Ando, Kenji; Yoshida, Tomoharu
Abstract: Although previously reported as relatively rare, esophageal hematoma can likely develop in patients on anticoagulants or those with underlying hemorrhagic disorders. From April 2018 to December 2018, among 36 patients who received transcatheter mitral valve edge‐to‐edge repair (TMVr) at our hospital, seven (19.4%), who were suspected of having digestive tract hemorrhage evidenced by blood stains on a probe extracted after transesophageal echocardiography, underwent esophagogastroduodenoscopy. Esophageal hematomas were noted in all patients, and endoscopic hemostasis was performed in two cases. Depending on their form, hematomas were noted on the submucosa and the epithelium of the shallow esophageal layer. Esophageal hematomas caused by transesophageal echocardiography for TMVr are not rare, and clinicians should be aware of it.